TIPE INDUSTRI DAN KUALITAS PENGUNGKAPAN EMISI KARBON DI INDONESIA - Ramadhani, Pavita; Venusita, Lintang (Jurnal Akuntansi AKUNESA, 2020)
The purpose of this research is to investigate the influence of industrial type on disclosure quality of carbon emission activity. Based on GICS classification this paper dividing industrial type into two, intensive firm and non-intensive firm.  This research?s sample are all the participants of sustainability report award from 2015-2017. The sample was selected using purposive sampling technique and obtained 89 companies. This paper used regression linear analysis with SPSS 24 for the analysis technique. The result of the analysisshows that industrial type significantly effect disclosure quality of carbon emission activity.